Gender and Power Representation in The Sit Still, Look Pretty By Daya: Sara Mills’ CDA - Mukminin, Muhamad Saiful; Zulfa, Ilma; Usman, Rizki Dwiki Reza; Irianti, Waviq Alfiana; Ramadhanti, Arviani Fayzaila (SALIENCE: English Language, Literature, and Education Journal, 2024)
The present research aims to analyze the representation of gender and power in the lyrics of Sit Still, Look Pretty by Daya using Sara Mills' critical discourse analysis. This research adopts a descriptive qualitative approach to explore the social phenomena reflected in the song lyrics and how they shape public perceptions of gender roles and power dynamics. The method used is critical discourse analysis, which emphasizes the relationship between language and power within the lyrics. The data for this study consists of the lyrics of Sit Still, Look Pretty, obtained from a valid source. Data collection was carried out through direct observation of the lyrics, which were then categorized based on the themes of gender and power. The data analysis technique employs Sara Mills' theory, focusing on the position of subjects and objects in the lyrics and the perspectives used. The findings reveal that the song portrays resistance to gender stereotypes and patriarchal norms. Daya positions women as independent subjects who reject traditional roles. This study concludes that the song reinforces values of female independence and challenges the patriarchal norms that remain dominant in society.